Development of a thermoelectric generator system for IoT applications - Wong, Wen Kang (2023)
Waste heat is produced as a by-product from various manufacturing process. In most of the industry, low-temperature waste heat is released into the atmosphere instead of recovering it due to low-grade heat energy that is unable to provide any useful work. Thermoelectric generator (TEG) is one of the waste heat recovery devices to generate electricity from the heat source. Along with the evolution of Industry 4.0, thermoelectric generator (TEG) encourages the acceptance of the recent technologies such as Internet of Things (IoT) devices into the manufacturing industry. IoT devices are the key components to build a powerful industrial system to boost the production rate. This is done by using real-time data to optimise the manufacturing process. However, installation of IoT system is costly as they require power source and the production plant must be shut down for installation purpose. For this reason, TEG system provides a solution by eliminating power cable to power up the additional devices. A plug and play IoT device that is completely wireless can be fabricated where system is maintenance-free as it does not have any moving part. To achieve that, this study aims to recover low-temperature waste heat using TEG module and convert them into electricity to power up small IoT device. In this study, the power generated by different type of heat sink, thermal conductive paste and TEG module were compared. Then, the configurations of the TEG to generate sufficient electricity to power up small IoT device were compared. Lastly, a wireless sensor device powered up by TEG was developed. The power output of the TEG system for each design was measured to analyse the performance of each design. From the experiment, it was found that the height of the fins for the heat sink is critical where heat sink with higher fins height can dissipate heat at a faster rate. As a result, higher temperature gradient is achieved and power output by the TEG is higher. In addition, air flow of the system is having significant impact on the overall performance of the system. At the end of this study, a feasible prototype of TEG system was built successfully. It managed to operate at surface temperature of 115 °C and above and atmospheric temperature of 30 °C.